Whose Vote Counts for Crime Policy? Group Opinion and Public Representation in Mass Incarceration, 1970–2015. - Duxbury, Scott W (Public Opinion Quarterly)
Policy responsiveness to public opinion is necessary for democratic governance, yet research on crime policy responsiveness has focused on the public at large, overlooking variation in policy support among demographic bodies and its heterogeneous effects on policy implementation. Creating new state-level measures of group opinion on punitive policy mood using 257,356 responses to 79 national surveys administered between 1970 and 2015, this study examines the effect of race, age, and gender-specific opinion on the incarceration rate. Consistent with prior studies, results reveal parallel trends in punitive policy support, with punitiveness increasing in tandem across demographic subgroups. Statistical findings from error correction models, however, reveal that not all groups had equal influence. Only the opinions of the most punitive groups—whites, men, and 30–44-year-olds—influenced the incarceration rate. Further, the largest divide in policy responsiveness to group opinion was between blacks and whites. In fact, estimates suggest that if whites' punitive policy support had not risen, the current incarceration rate would be roughly the same as if violent crime had not risen during the 45 years of mass incarceration. The implications of these results are discussed for research on policy responsiveness, partisan politics, and for the "democracy at work" hypothesis of mass incarceration.